The genetic and clinical characteristics and effects of Canakinumab on cryopyrin-associated periodic syndrome: a large pediatric cohort study from China - Shu, Zhou; Zhang, Yue; Han, Tongxin; Li, Yan; Piao, Yurong; Sun, Fei; Ma, Jin; Mo, Wenxiu; Sun, Jiapeng; Chan, Koon-Wing; Yang, Wanling; Lau, Yu-Lung; et al. (Frontiers in Immunology, 2023)
Cryopyrin-associated periodic syndrome (CAPS) comprises a group of disorders characterized by recurrent bouts of systemic inflammation related to overactivation of inflammasome. So far, neither large cases of the correlation between genotype and phenotype nor treatment strategies have been clearly stated in China. Here, we studied the clinical and genetic characteristics and their correlation from 30 CAPS patients in China. We identified the pathogenesis for novel mutations by activating NLRP3 inflammasome for peripheral cells with ATP plus LPS, compared characteristics with other case series, and analyzed treatment outcomes of these patients. The patients harbored 19 substitutions in NLRP3, and 8 of them were novel mutations. Among these novel mutations, percentages of severe musculoskeletal, ophthalmologic, and neurological symptoms were higher compared with other case serials. The correlation of phenotypes and their variants seemed different in our cases, such as T350M, S333G/I/R, and F311V (somatic mosaicism). Ten patients received Canakinumab treatment, which proved effective at alleviating musculoskeletal, neurological, auditory, visual manifestations, fever, and rash for 10–20 months follow-up. Patients treated with prednisolone or prednisolone plus thalidomide or methotrexate, tocilizumab, TNF inhibiting agents, and sirolimus achieved only partial remission. Importantly, we firstly identified somatic mosaicism mutation of F311V, which was severe. Our study extended the spectrum of genotype and phenotype and characteristics of their correlations and provided detailed responses to different treatment strategies. These data provide guidance for future diagnosis and management for CAPS.